Assessment of positive psychological functioning among Chinese university students: Revision and psychometric properties of a psychological capital scale - Yanlan Chen; Xiaowei Feng; Syed Kamaruzaman Syed Ali; Hutkemri Zulnaidi (PLoS ONE, 2025)
Psychological capital serves as a psychological asset facilitating personal growth and enhanced performance. It aids individuals in navigating life’s myriad challenges and adversities, promoting psychological well-being and adaptability. Despite the widely recognized importance of psychological capital in enhancing competitiveness and work performance, existing assessment tools, such as the PCQ-24 developed by Luthans et al. (2007), have not been adequately validated in the Chinese university student population. To explore the factor structure of the Psychological Capital Questionnaire (PCQ-24) developed by Luthans et al., the researchers employed Principal Component Analysis (PCA) and Exploratory Factor Analysis (EFA), extracting factors with eigenvalues greater than 1. The results revealed a six-factor structure, which is inconsistent with the original four-factor structure of the PCQ-24 measurement tool. Therefore, Luthans’ psychological capital scale is not suitable for university students. Additionally, the indigenous scale developed by Chinese researchers Ke Jianglin et al (2009) is more suitable for organizational employees rather than university students. Hence, it is essential to revise and validate a psychological capital measurement tool appropriate for Chinese university students. To fill this gap, the researchers aimed to revise and validate a psychological capital scale suitable for Chinese university students based on the four structural dimensions proposed by Luthans et al. In this study, a large-scale survey of Chinese university students (N = 2780) was conducted, and SPSS 26.0 and AMOS 24.0 were used to statistically analyze the data and assess the psychometric properties of the Revised Mental Capital Scale. The results indicate that the revised psychological capital scale meets the psychometric requirements. The study concluded that the psychological capital scale revised and validated by the researcher can be used as an instrument to measure and assess the psychological capital of university students.